The Prayer of Jabez - Wilkinson, Bruce; Nang Chan Yeema (Nashville , TN USA Thomas Nelson, Inc., 2001)
Retells, in the form of a rhyme, the Old Testament story of Jabez, who learned how powerful prayer can be.
Keywords: Juvenile Nonfiction